MANAJEMEN AKTIVITAS MEDIA SOSIAL AKUN INSTAGRAM @INDONESIABAIK.ID [Manajemen Aktivitas Media Sosial Akun Instagram @indonesiabaik.id] - Rizky Pratama Hajati; Susie Perbawasari; Hanny Hafiar (Universitas Lambung Mangkurat, 2018)
ABSTRACT Indonesiabaik.id is a site managed by Ministry of Communication and Informatics and create a team named indonesiabaik.id. The IndonesiaBaik.id team focuses on news which can target the age of 20-34 years. In conducting its activities IndonesiaBaik.id team uses several social media one of them Instagram. However, his lack of engagement becomes an obstacle in managing Instagram social media. This study aims to find out how the management of social media Instagram @ indonesiabaik.id through the stage of disseminate (share), optimize (optimize), manage (manage), and engage (engage). This research uses desscriptive method. Technique of collecting data of in-depth interview, observation and literature study. In this study it was concluded that in the management of Instagram @ indonesiabaik.id account at the share stage ran to Inpres no. 9 of 2015 Ministry of Communications in absorbing public aspirations. But @ indonesiabaik.id not yet optimal in building public trust. At the optimization stage of monitoring conducted to find out what is in the public by talking about @ indonesiabaik.id done by manual that is mention check and hashtag. In the manage phase, indonesiabaik.id has done some things such as doing monitoring media, responding to quick comments and interacting in the real time. But in this stage @ indonesiabaik.id not using social media tools mention The last stage is engage, in this stage @ indoneisbaik.id not have influencer, then indonesiabaik.id also to reach its audiences using quiz. Grabbed his audience too admin Instagram account actively reply to his own comments to make his comments active. Keywords: Social media, Instagram, Government, team @indonesiabaik.